FAKTOR KREDIT PERBANKKAN BERMASALAH/ NON PERFORMING LOAN PERBANKAN PONOROGO - Prihatin, Lilik; Sudarwanto, Albertus Sentot, Pujiyono (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2018)
Abstract The objective of this article is to investigate the non-performing loan factors. In distributing loans, many problems occur in the form of non-performing loans which cause disadvantages to banks. This article used the empirical/non-doctrinal research method. The result of the study shows that the loan applicants have not used the given loans in accordance with its intention, in which the loans are used to finance other businesses or to finance consumption. Due to the bank customers’ less ability to manage their businesses, due to their incomprehensio/ignorance to their business prospects, and/or due to the rift in their marriages/divorces, the debtors are no longer able to pay the deferred payments, and therefore they are unable to be responsible for the loan settlement. Keywords: Factors non-performing loan, relations between banks and customers Abstrak Artikel ini bertujuan untuk mengetahui faktor kredit perbankan bermasalah/non performing loan, dalam penyaluran kredit bank banyak mengalami permasalahan kredit macet/kredit bermasalah yang mengakibatkan pihak bank merasa dirugikan. Jenis artikel dalam penulisan ini adalah empiris/non-doktinal. Berdasarkan hasil penelitian dan pembahasan dapat disimpulkan bahwa: Pengguna kredit tidak sesuai dengan tujuan penggunaannya, dimana tujuan pemberian kredit digunakan untuk usaha lain atau untuk keperluan yang konsumtif, Nasabah kurang mampu mengelola usahanya tersebut, juga disebabkan ketidaktahuan/ketidakfahaman debitur akan prospek usaha yang dijalankannya, serta keretakan rumah tangga/cerai, dimana debitur sudah tidak sanggup lagi melunasi angsuran sehingga pelunasannya tidak bertanggungjawab lagi. Kata Kunci : Faktor Kredit Bermasalah, Hubungan Bank Dengan Nasabah